2014
DOI: 10.5539/elt.v8n1p155
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies Employed by Chinese English-Major Pre-Service Teachers in Relation to Gender and Personality Types

Abstract: This study was intended to investigate the use of language learning strategy employed by English-major pre-service teachers in Midwest China in relation to their gender and personality types. The modified Strategy Inventory for Language Learning (SILL) and adopted personality type inventory were used to collect the data. ANOVA and Chi-square tests were performed for data analysis. The results revealed that gender and personality types have some effects on pre-service teachers' strategy use at the overall, cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The results showed that the LLSs overall use of participants was medium to high with mean statistics ranging between M=3.75 and M=2.88 and a mean in overall use of 3.37 (table 1.). This result is in line with other recent studies in Spain and other countries (Feng, 2010;Franco Naranjo et al, 2003;Franco Naranjo et al, 2009;García Herrero, 2013;García Herrero & Jiménez Vivas, 2014;Ghavamnia, et al, 2011;Hong-Nam & Leavell, 2006;Kavasoglu, 2009;Nikoopour et al, 2012;Razak & Babikkoi, 2014;Zhou & Intaraprasert, 2015). The scores in the different categories indicate a positive attitude towards the use of LLSs among the participants while learning English as a foreign language.…”
Section: Overall Usesupporting
confidence: 81%
See 2 more Smart Citations
“…The results showed that the LLSs overall use of participants was medium to high with mean statistics ranging between M=3.75 and M=2.88 and a mean in overall use of 3.37 (table 1.). This result is in line with other recent studies in Spain and other countries (Feng, 2010;Franco Naranjo et al, 2003;Franco Naranjo et al, 2009;García Herrero, 2013;García Herrero & Jiménez Vivas, 2014;Ghavamnia, et al, 2011;Hong-Nam & Leavell, 2006;Kavasoglu, 2009;Nikoopour et al, 2012;Razak & Babikkoi, 2014;Zhou & Intaraprasert, 2015). The scores in the different categories indicate a positive attitude towards the use of LLSs among the participants while learning English as a foreign language.…”
Section: Overall Usesupporting
confidence: 81%
“…More recently there have been a number of studies supporting the superiority of female learners in overall strategy use, and in specific categories (Alhaisoni, 2012;C.-Y. Chang, Liu, & Lee, 2007;Corpas Arellano, 2010;Ghee, Ismail, & Kabilan, 2010;Hong-Nam & Leavell, 2006;Kavasoglu, 2009;Khalil, 2005;Radwan, 2011;Zhou & Intaraprasert, 2015).…”
Section: Llss and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Key Terms of the Present Study Language Learning Strategies In the present study, "language learning strategies" have been considered as "some general approaches or specific actions/techniques, whether observable or unobservable, which Chinese English-major pre-service teachers generate and make use of to enhance their English language learning directly or indirectly (Zhou & Intaraprasert, 2015, p. 156)".…”
Section: A Key Terms Used In the Present Studymentioning
confidence: 99%
“…English-major pre-service teachers "English-major pre-service teachers" refer to "students majoring in English in Normal Universities in China, whose career orientation will be primary or middle school English teachers after graduation (Zhou & Intaraprasert, 2015, p. 156)". Students need to be trained for 4 years in these Normal Universities.…”
Section: A Key Terms Used In the Present Studymentioning
confidence: 99%